2005
DOI: 10.1007/s00440-005-0475-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase ordering after a deep quench: the stochastic Ising and hard core gas models on a tree

Abstract: ABSTRACT. Consider a low temperature stochastic Ising model in the phase coexistence regime with Markov semigroup Pt. A fundamental and still largely open problem is the understanding of the long time behavior of δηPt when the initial configuration η is sampled from a highly disordered state ν (e.g. a product Bernoulli measure or a high temperature Gibbs measure). Exploiting recent progresses in the analysis of the mixing time of Monte Carlo Markov chains for discrete spin models on a regular b-ary tree T b , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Now using Azuma's inequality, there exist constants c 1 , c 2 ∈ R + such that It follows by an application of Boole's inequality that there exists a constant c ∈ R + such that (29) holds.…”
Section: Appendixmentioning
confidence: 99%
“…Now using Azuma's inequality, there exist constants c 1 , c 2 ∈ R + such that It follows by an application of Boole's inequality that there exists a constant c ∈ R + such that (29) holds.…”
Section: Appendixmentioning
confidence: 99%
“…Morris [28] has shown that p * converges to 1/2 as d → ∞. Caputo and Martinelli [29] have shown the same result for d-regular trees, while Kanoria and Montanari [30] derived it for d-regular trees in a synchronous setting where flips occur simultaneously, and obtained lower bounds on p * (d) for small values of d. The case d = 1 was first investigated by Erdös and Ney [31], and Arratia [32] has proven that p * (1) = 1.…”
Section: B Contributionmentioning
confidence: 98%
“…It is also easy to see that M 0 = E[W ] = N/2, and M N = W . We also have It follows by an application of Boole's inequality that there exists a constant c ∈ R + such that (29) holds.…”
Section: Appendixmentioning
confidence: 99%
“…Indeed, Howard [21] showed that p c (T 3 ) > 1/2, and it was proved by Caputo and Martinelli [13] that p c (T d ) → 1/2 as d → ∞ (in fact their result is more general, and this statement is straightforward to prove in the zero-temperature case), but for every d ≥ 4 it is unknown whether or not p c (T d ) = 1/2. For further results and problems about the case p = 1/2, on Z d and on other graphs, see for example [12,21,29,32,33]; for a good account of Glauber dynamics at non-zero temperatures, see [25].…”
Section: Introductionmentioning
confidence: 94%